PRESEPSI MASYARAKAT TENTANG KEBERADAAN ODONG-ODONG DIKAMPUNG PASAR GOMPONG NAGARI KAMBANG BARAT KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Novita, Winda - (Pendidikan Geografi, 2014)
This research wasmotivated bythe presencein the village odong-odong Gompong Pasar Nagari Kambang Western District of Pesisir Selatan District Lengayang conducting public perception. This studyaims to determinethe dataor informationan danalyzethe datain depth aboutpublic perception ofthe conditionandthe impacton thevillage odong-odong Gompong Pasar Nagari Kambang Barat Lengayang District of Pesisir Selatan District. The research is aqualitative study using purposive sampling technique. Furthermore, the datacollected through interview,observation and do cumentation, afterthe datawere obtained, the data were analyzed through himaging techniqueswords.The resultsofthe research fieldasfollows: 1) Public perception ofthe condition odong-odong isable tofita lot ofpeople on board, if thepolicedo not allowodong-odong drivingon the highwayin case ofaccident odong-odong whobearits ownthen the police willgi vesanctionif theviolation of the rulesbut the factthat odong-odong alsoinhigh way driving. 2) In addition,the impactonthe public perception ofodong-odong having positive and negative effectsfor societyodong-odong are: a) The positive impactis asa means of transportationand tourismfor the people inthe village of Nagari Kambang Gompong Pasar Barat. b) The negative impactthatan accident couldo ccuranddisrupt the activities ofthe community.